2005
DOI: 10.1073/pnas.0406731102
|View full text |Cite
|
Sign up to set email alerts
|

A role for transferrin receptor in triggering apoptosis when targeted with gambogic acid

Abstract: Transferrin receptor (TfR) has been shown to be significantly overexpressed in different types of cancers. We discovered TfR as a target for gambogic acid (GA), used in traditional Chinese medicine and a previously undiscovered link between TfR and the rapid activation of apoptosis. The binding site of GA on TfR is independent of the transferrin binding site, and it appears that GA potentially inhibits TfR internalization. Down-regulation of TfR by RNA interference decreases sensitivity to GA-induced apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
167
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(173 citation statements)
references
References 26 publications
3
167
2
Order By: Relevance
“…This result suggests the presence of other targets aside from p53. In addition, a recent study from Kasibhatla et al (25) and Pandey et al (34) showed that transferrin receptor (CD71), an iron-transport protein that was highly expressed in tumor cell membrane, was the ligand of GA, leading to mitochondria-dependent and mitochondriaindependent apoptosis pathway activation by GA. Therefore, we examine the involvement of CD71 using siRNA to knock down CD71.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests the presence of other targets aside from p53. In addition, a recent study from Kasibhatla et al (25) and Pandey et al (34) showed that transferrin receptor (CD71), an iron-transport protein that was highly expressed in tumor cell membrane, was the ligand of GA, leading to mitochondria-dependent and mitochondriaindependent apoptosis pathway activation by GA. Therefore, we examine the involvement of CD71 using siRNA to knock down CD71.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, GA induced cancer cell G 2 -M phase arrest and repressed telomerase reverse transcriptase (23,24). Recently, Kasibhatla et al showed that transferrin receptor (TfR or CD71) is the target protein of GA (25). All studies reported to date show that GA is a potent anticancer agent with diverse molecular targets through different mechanisms (26).…”
Section: Introductionmentioning
confidence: 99%
“…The resin has been used in traditional Chinese medicine for the treatment of cancers (15). It has potent anticancer activity because of its activation of the apoptotic pathways in cancerous cells (16)(17)(18)(19). Recently, it has been reported that GA triggers apoptosis upon binding to the transferrin receptor (20).…”
mentioning
confidence: 99%
“…It is known that caspase-8 and caspase-9 are activated by the death receptor signaling pathway and the mitochondrial signaling pathway during apoptosis in order, whereas caspase-3 is a common effector of both signaling pathways. 33,34 Therefore, we speculate that the LCL-HHT-H-PEG might induce MM CSC apoptosis via mitochondrial apoptotic pathway. This was because the LCL-HHT-H-PEG formulation enhanced the expression of the initiator caspase-9 and the executioner caspase-3, which led to MM cell apoptosis.…”
Section: Lcl-hht-h-peg Induces the Apoptosis Of MM Cells In Vivo And mentioning
confidence: 99%